2018
DOI: 10.1590/1806-90882017000600008
|View full text |Cite
|
Sign up to set email alerts
|

ABOVEGROUND BIOMASS GROWTH AND YIELD OF FIRST ROTATION CUTTING CYCLE OF Acacia AND Eucalyptus SHORT ROTATION DENDROENERGY CROPS

Abstract: -Chile has strong interest in biomass production for the purpose of generating bioenergy to accomplish environmental standards for clean energy production. However, no yield or productivity information is available about forest crop plantations established at high-initial planting densities dedicated to energy production. The objective of the present study was to provide long-term results of short-rotation forest crops research trials, investigating first cutting cycle most promising species biomass production… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
2
3
0
3
Order By: Relevance
“…A power-law growth curve represented the changes in AGB with increasing woodlot age well for the studied stands between one and nine years of age (Figure 3). Our findings are in line with several previous studies in monocultural short-rotation tree plantations showing similar relationships (e.g., [44,78,89,90]).…”
Section: Controls Of Biomass and Growth Of M Dubiasupporting
confidence: 93%
“…A power-law growth curve represented the changes in AGB with increasing woodlot age well for the studied stands between one and nine years of age (Figure 3). Our findings are in line with several previous studies in monocultural short-rotation tree plantations showing similar relationships (e.g., [44,78,89,90]).…”
Section: Controls Of Biomass and Growth Of M Dubiasupporting
confidence: 93%
“…4.3). Our findings are in line with several previous studies in monocultural short-rotation tree plantations showing similar relationships (e.g., Paula et al, 2013;Arora et al, 2014;Acuña et al, 2017).…”
Section: Controls Of Biomass and Growth Of M Dubiasupporting
confidence: 93%
“…(2010) compared acacia species with other short-rotation common Southern European countries crops, such as Italy, from a techno-economic perspective of production viability [38]; Lenis et al (2013) also studied the use of short-rotation crops for bioenergy with acacias and eucalyptus in Colombia, but focused more on the perspective of the physico-chemical properties of derived fuels and their potential for energy recovery [39]. This dispersion of studies and research work, examples of which can be found in Brazil [40][41][42], South Africa [43,44], China [45,46], in addition to those already widespread in Europe or the United States of America [47,48], highlights the need for these regions over the past few years to control the dispersion of species belonging to a genus originating mainly from Australia, which has spread to practically all regions of the world, causing serious problems to the local biodiversity, as they enter into direct competition with indigenous species [49].…”
Section: Resultsmentioning
confidence: 99%